Prototype terminal aerodrome forecasts using a mesoscale model - Edwards, Benjamin I., author (Colorado State University. Libraries, 1993)
The purpose of this study is to evaluate the potential of the Regional Atmospheric Modeling System (RAMS) in this configuration to forecast convective cloud coverage, timing, location, and precipitation on a mesoscale grid. Using this model output a prototype terminal aerodrome forecast (TAF) has been produced. RAMS was developed at Colorado State University and is being used to simulate convection over central Florida using a nested grid model where the smallest grid had a horizontal spacing of 5 kilometers. To obtain meaningful results a 2.5w cumulus parameterization scheme was used. The traditional cumulus parameterization schemes assume that the effect of convection is limited to one grid box, this assumption does not apply on grid spacings of 5 kilometers. The model was evaluated using data collected by the Convection and Precipitation Electrification Experiment (CaPE) over Florida during the summer of 1991. The model performed a 12 hour forecast valid from 12Z on 29 July 1991 to 00Z on 30 July. The course grid had a horizontal grid spacing of 80 kilometers and covered an area from Washington D.C. south to the western edge of Hispaniola and west to Fort Worth Texas and north to Topeka Kansas. This area includes most of the Gulf of Mexico and extends 200 kilometers east of Cape Hatteras North Carolina. The second grid has a horizontal grid spacing of 20 kilometers and covers the Florida peninsula and adjacent coastal waters. The third grid was centered over the Kennedy Space Center Florida and is approximately 40 kilometers north, west, and south and 20 kilometers east over the ocean. The placement and size of the third grid was used to evaluate the usefulness of a producing model-aided TAF's. One of the problems facing the forecasting community is how to prepare a TAF, the aviation communities forecast, with the current NWP products. Currently forecasters use the Nested Grid Model (NGM) with a horizontal grid spacing of 80 kilometers. The resolution of the NGM is 320 kilometers and is totally inadequate for the task of preparing an aviation forecast. Aviation forecasts are valid for the weather within 20 kilometers of the runway. The NGM parameterizes convection on this scale while the 2.5w parameterization can explicitly resolve features on the 5 kilometer scale. This increased resolution will greatly aid in the production of aviation forecast. As a demonstration the RAMS model output will be used to produce a TAF for Kennedy Space Center.
December 14, 1993.
Also issued as author's thesis (M.S.) -- Colorado State University, 1993.
Keywords: Weather forecasting; Mesometeorology; Convection (Meteorology)